Lesson study in continuing professional teacher develop-ment: a South African case study - Coe, Karen; Carl, Arend; Frick, Liezel (University of the Free State, 2010)
English: The implementation of successful continuing professional teacher development (CPTD) programmes has been a challenge in South Africa since the introduction of Curriculum 2005. Lesson study, a CPTD model introduced in Japan and not previously investigated in South Africa, has shown success in bridging the gap between policy at the national level and teaching at the classroom level. A qualitative research study conducted in a rural primary school in the Western Cape province sought to determine the value that a group of teachers would place on the process of lesson study as a model for their own learning and instructional improvement. The findings highlight several areas where lesson study as a dynamic model can be considered an effective CPTD programme within the South African context.

Afrikaans: The implementation of successful continuing professional teacher development (CPTD) programmes has been a challenge in South Africa since the introduction of Curriculum 2005. Lesson study, a CPTD model introduced in Japan and not previously investigated in South Africa, has shown success in bridging the gap between policy at the national level and teaching at the classroom level. A qualitative research study conducted in a rural primary school in the Western Cape province sought to determine the value that a group of teachers would place on the process of lesson study as a model for their own learning and instructional improvement. The findings highlight several areas where lesson study as a dynamic model can be considered an effective CPTD programme within the South African context.
Keywords: Professional teacher development; Curriculum 2005